Cobrindo e descobrindo Lolita: as capas como traduções intersemióticas do romance de Nabokov - Lazarin, Denize Helena (2018)
This research aims to investigate text-paratext relationship in Lolita’s covers from an intersemiotic translation perspective. We know that Lolita is a highly mediatized character, and that with the success of Nabokov’s novel she began to inhabit the most diverse media, assimilating the most diverse meanings. The covers of the work, both the commercial ones and those from the contest hold by Bertram in 2011, that constitute our corpus, are emblematic examples of these varied readings. Based on the covers as intersemiotic translations of the work, we perceive a complex dynamics. Whereas publishers need eye-catching covers to attract readers, the covers cannot shy away from their commitment as the work's paratext. So we wondered how, and if, they can escape the easily commercial and still be attractive. As well as if they only endorse the point of view of the narrator or do they contemplate other elements, such as the voice of the oppressed? Our hypothesis is that while some covers of greater commercial appeal endorse the perspective of the narrator, others, especially from the contest, manage to address other elements. In an attempt to answer these questions and verify whether or not the assumptions are confirmed, we divide our text into five chapters. In the first we investigated the history of the cover from the beginning. Moreover we approached the cover issue as a part of the work, as well as its relation with the publishing market, giving an example of what happened in Lolita. In the second chapter we deal with the transmutation from verbal into visual, through intermediality to intersemiotic translation in cover design. In the third one we investigate the character, emphasizing their survival beyond literature. In chapter four we discuss the critical fortune of the novel in order to verify the main trends pointed out by literary criticism. Finally, in the fifth chapter, we created a table for comparative analysis of the covers from two other existing ones. In general, we realize that while most of the commercial selected covers give the privilege of portraying the nymphet from the point of view of a partial narrator, the covers from the contest approach more varied themes, even contemplating some elements ignored by the commercial ones.